Energy calibration through X-ray absorption of the DECAL sensor, a monolithic active pixel sensor prototype for digital electromagnetic calorimetry and tracking - Fasselt, Lucian; Allport, Philip Patrick; Benhammadi, Seddik; Bosley, Robert Ross; Dopke, Jens; Flynn, Samuel; Gonella, Laura; Guerrini, Nicola; Issever, Cigdem; Nikolopoulos, Kostas; Kopsalis, Ioannis; Philips, Peter; et al. (Frontiers in Physics, 2023)
In calorimetry, the predominant detection principle is to measure the energy deposited by particles within a shower initiated by an incident particle. An alternative concept is a sampling calorimeter where the highly granular active layers rather measure the number of secondary particles in the shower by detecting hits through binary readout similar to sensors for tracking applications. In this context, the DECAL sensor is a fully-depleted monolithic active pixel sensor prototype with reconfigurable readout for digital electromagnetic calorimetry and tracking. Its 64 × 64 pixels with a pitch of 55 µm are fabricated in a modified TowerJazz 180 nm CMOS imaging process using a 25 µm epitaxial silicon layer. The readout at 40 MHz is configurable in counting hits in the sensor grouped as either 64 strips or 4 pads. In this article, we present the energy calibration of this sensor using a gamma source of americium-241 as well as X-ray fluorescence at various wavelengths. The uniformity of the pixel responses is shown, allowing the summation of counts across all pixels. By that, two standalone energy calibration methods are developed that describe the X-ray absorption in the energy range of 4 to 60 keV and agree with each other.